Design and Development of a Tractor Mounted Sweet Potato Transplanting Machine - Mohamed El Hassan, Mansour Widaa (2001)
Transplanting is an important method of establishing field sweet potatoes. Design of a suitable transplanting machine depends on transplanting method. A design concept for the sweet potato transplanting machine was developed using Auto CAD R14. A prototype transplanter was designed, fabricated and field tested at the Department of Biological and Agricultural Engineering, UPM, Serdang, Malaysia. The overall construction of the machine consists of the main chassis, power transmission system, transplanting pocket and handling system of the sweet potatoes vine cuttings. The machine was ground driven and mounted on the 3-point hitch linkage system of a mini or medium size tractor of 20-40 kW. Two operators were required in the transplanting operation; a driver for the tractor and an operator to feed the sweet potato seedlings manually. The operational activities for the machine include the preparation of planting furrow, placement of seedlings horizontally in the prepared furrow, covering of the seedlings and compacting the soil around the planted seedlings. The machine allowed all possible variations and component adjustments to ensure prompt and comprehensive field evaluation. The power requirement was about 8.9 kW for a single row machine. The machine was simple in design, easily manufactured locally and able to operate at high efficiency (77%). Forward speeds were significant parameter for transplanting and machine efficiency. These experimental results showed that first speed of 2km/hr together with planting depth of 20cm is the best among speeds and depths tested as it gave the lower number of missing plants. The sweet potato transplanting machine had an average capacity of 0.19 ha/hr at low speed (2km/hr) while the vegetable transplanter had about 0.09 ha/hr at the same speed. The expected yield for this machine should be greater than the yield produced vertically.